Mempertemukan Agama Lokal Dan Kekristenan dalam Bingkai Kontekstualisasi dan Poskolonial. - Maria Magdalena Bire Logo (APOSTOLOS, 2022)
This article discusses local religions that long before the arrival of Christianity had a concept of the Divine. Christianity, which removed culture, in its development, actually opened itself to accept culture in religious rituals such as forming a culture and language month at GMIT. As contextualization. In addition to contextualization efforts, postcolonialism takes on a role in criticizing western Christianity which oppresses culture as a product of the third world. This article uses qualitative research methods by conducting field research with an ethnographic approach and literature research using group research reports that examine ethnic groups in NTT. From this study it was found that the concept of the Divine from local religions has a strong bond with nature. Contextualization that tries to use cultural elements to introduce Christianity can actually be ambiguous in syncretism. Meanwhile, postcolonial offers cosmoteandric as a wider scope to tie the relationship between God, humans, and the cosmos.